(untitled) (Bangladesh Journal of Public Administration, 2021)
After departing from the ideologies of traditional public administration, Bangladesh has experienced quite a few innovations in public administration. A practical illustration of that is the establishment of the Governance Innovation Unit under the prime minister’s office and the A2i at the ICT division, the first innovation laboratory of its kind in the world. At the same time truly remarkable are the innovations achieved with the help of technology and information in the public sector, especially for a young country such as Bangladesh. Usage of technology is hoped to reduce the rigidity of service delivery, increase effectiveness and efficiency, and also at the same decrease the travel, cost, and visit for the service recipients. Institutionalization of these innovations is vital for making the innovations replicable throughout the whole sector and also for making them sustainable. This paper aims to examine and understand the state of institutionalization of technological innovations in the public sector of Bangladesh, investigate the strategies that are helping to attain that goal, and understand the challenges to the process of institutionalization. The design of the paper is qualitative as it employs rigorous content and document analysis and also incorporates data from expert interviews. The paper concludes with the remark that; Bangladesh has a long way to go in regard to institutionalize the innovations it has been taken and a particular set of planned strategies must be taken to make the innovations sustain and embed in the organizational culture of the public sector in Bangladesh.